Anatomic Site-Specific Complication Rates for Central Venous Catheter Insertions. (September 2020) - Bell, Jacob; Goyal, Munish; Long, Sallie; Kumar, Anagha; Friedrich, Joseph; Garfinkel, Jonathan; Chung, Suzi; Fitzgibbons, Shimae
Background: Central venous catheter (CVC) complication rates reflecting the application of modern insertion techniques to a clinically heterogeneous patient populations are needed to better understand procedural risk attributable to the 3 common anatomic insertion sites: internal jugular, subclavian, and femoral veins. We sought to define site-specific mechanical and duration-associated CVC complication rates across all hospital inpatients. Methods: A retrospective chart review was conducted over 9 months at Georgetown University Hospital and Washington Hospital Center. Peripherally inserted central catheters and tunneled or fluoroscopically placed CVC's were excluded. Mechanical complications (retained guidewire, arterial injury, and pneumothorax) and duration-associated complications (deep vein thrombosis or pulmonary embolism, and central line-associated bloodstream infections) were identified. Results: In all, 1179 CVC insertions in 801 adult patients were analyzed. Approximately 32% of patients had multiple lines placed. Of 1179 CVCs, 73 total complications were recorded, giving a total rate of one or more complications occurring per CVC of 5.9%. There was no statistically significant difference between site-specific complications. A total of 19 mechanical complications were documented, with a 1.5% complication rate of one or more mechanical complications occurring. A total of 54 delayed complications were documented, with a 4.4% complication rate of 1 or more delayed complications occurring. There were no statistically significant differences between anatomic sites for either total mechanical or total delayed complications. Conclusions: These results suggest that site-specific CVC complication rates may be less common than previously reported. These data further inform on the safety of modern CVC insertion techniques across all patient populations and clinical settings.